2014
DOI: 10.1111/iej.12260
|View full text |Cite
|
Sign up to set email alerts
|

Effects of NaOCl, EDTA and MTAD when applied to dentine on stress distribution in post‐restored roots with flared canals

Abstract: NaOCl-, EDTA- and MTAD- treated dentine and a rigid post with high elastic modulus may increase fracture risk in roots with flared canals by increasing the stresses within root dentine. Therefore, solutions that alter the elastic modulus of dentine less (such as NaOCl) or an individually shaped post-core system constructed with a material that has an elastic modulus close to dentine (polyethylene fibre) should be used in weak roots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 57 publications
(146 reference statements)
2
8
0
1
Order By: Relevance
“…The results of our study support the findings in the literature that EDTA exerts negative effects on the mechanical properties of dentin (10,18–21). Although EDTA showed no statistical difference in the dentin flexural strength test, when compared to the other study groups, EDTA resulted in lower strength values than in the control group in the dentin cohesive strength and root fracture tests.…”
Section: Discussionsupporting
confidence: 91%
“…The results of our study support the findings in the literature that EDTA exerts negative effects on the mechanical properties of dentin (10,18–21). Although EDTA showed no statistical difference in the dentin flexural strength test, when compared to the other study groups, EDTA resulted in lower strength values than in the control group in the dentin cohesive strength and root fracture tests.…”
Section: Discussionsupporting
confidence: 91%
“…The post and core with high elastic modulus may increase fracture risk in roots with flared canals by increasing the stresses within root dentin. Therefore, an individually shaped post-core system constructed with a material that has an elastic modulus close to dentin should be used in weak roots 15) . The fracture resistance strength of the metal cast post-and-core is obviously larger than that of the single prefabricated fiber postand-core, which is similar to the results of Varvara et al 16) .…”
Section: Discussionmentioning
confidence: 99%
“…According to Belli et al [3], the elastic modulus of the material used for IRs influences the fracture resistance because a post and core with a high elastic modulus generate a greater concentration of stresses on the root dentin, resulting in an increased risk of fracture of the IR-tooth system. erefore, the preceding study suggested that a post and core system using a material with an elastic modulus similar to that of dentin should be implemented to ensure adequate stress dissipation and thus avoid areas of concentrated stress in the walls of the root that can generate failures at the post-cement-dentin interface or radicular fractures [3,26]. From this perspective, glass fiber systems have shown excellent biomechanical behavior compared to other materials [27].…”
Section: Agreements and Disagreements With Other Studies Ormentioning
confidence: 99%